80 The direct effects of inorganic nitrite on left ventricular function in humans: an invasive pressure-volume loop study. (May 2019) - O'Gallagher, Kevin; Cabaco, Ana Rita; Roomi, Ali; Ryan, Matthew; Dancy, Luke; Hoare, Amy; Melikian, Narbeh; Chowienczyk, Phil; Webb, Andrew; Shah, Ajay
Abstract : Introduction: Inorganic nitrite is a potential nitric oxide (NO)-augmenting therapy that is of considerable interest due to the lack of tolerance to its effects, in contrast to organic nitrates. Previous work has shown that NO has beneficial effects on myocardial relaxation and diastolic function while abnormalities of NO-cGMP signalling are implicated in Heart Failure with Preserved Ejection Fraction (HFpEF). Systemic preparations of inorganic nitrite have therefore been tested in small clinical trials for its effects in patients with HFpEF. In humans, nitrite is an arterial dilator, demonstrating selectivity for conduit arteries over resistance arterioles but its direct cardiac effects in vivo have not been established. We hypothesised that intracoronary inorganic nitrite has direct beneficial effects on cardiac diastolic function. Methods: 20 patients with angiographically normal coronary arteries and normal left ventricular function were given an intracoronary infusion of sodium nitrite (8.7 micromol/min for 5 min, followed by 26 micromol/min for 5 min). LV pressure-volume relations were obtained via a micromanometer-conductance catheter, with recordings taken at baseline and after each dose of nitrite. The primary end-point was change in LV End-diastolic pressure (LVEDP). Secondary end-points included other indices of LV diastolic and systolic function. Statistical analyses were performed using ANOVA for repeated measures (or non-parametric equivalent) with multiple comparison testing, reported as mean [95% CI] unless otherwise specified. Results: Intracoronary nitrite was associated with a significant dose-dependent decrease in LVEDP (P=0.001). The 26 micromol/min dose of nitrite resulted in a decrease of 1.9mmHg [0.5, 3.3] P=0.006 versus baseline and a decrease of 1.1mmHg [0.2, 2.1], P=0.02 versus 8.7 micromol/min nitrite. There were also significant decreases in the time to LV end-systole (LVEST, P=0.004, with 26micromol/min nitrite resulting in a decrease of 11ms [4, 18] P=0.002 versus baseline) and the LV end-diastolic pressure-volume relation (EDPVR, P=0.006). No significant changes in dP/dtmin (P=0.2) or tau (P=0.3) were seen. The changes in diastolic function occurred without any associated change in mean arterial pressure, heart rate or LV systolic function (all p=NS). Conclusion: Intracoronary Inorganic nitrite exerts a direct effect on LV diastolic function in humans, independent of changes in systolic function or blood pressure. Inorganic nitrite affects both the onset of relaxation and LV end-diastolic properties. These data indicate that the direct cardiac effects of inorganic nitrite contribute significantly to the overall effects of systemically-delivered nitrite and have potential implications for patients with LV diastolic dysfunction and HFpEF. Supported by the MRC, BHF and GSTT/KCL NIHR Biomedical Research Centre. Conflict of Interest: Nil